1996
DOI: 10.1007/bf02278252
|View full text |Cite
|
Sign up to set email alerts
|

Criterion validation of two approaches to performance appraisal: The behavioral observation scale and the relative percentile method

Abstract: ABSTRACT." We compared the criterion validity of a new "relative" performance appraisal format (percentile-based ranking) to that of an "absolute" format (BOS) in a sample of 88 unit managers. Overall, our results suggest that the relative format has higher criterion-related validity than does the absolute format. These findings contradict conventional wisdom that format-related differences in measures of performance are minimal and that relative approaches to performance appraisal are inferior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 9 publications
3
93
0
1
Order By: Relevance
“…Evidence shows that the RPM can achieve a greater range of-and more accuratescores when compared with rating each student independently. 9 The three domain ratings were strongly correlated with one another (r = 0.71-0.84, P < .001). A principal components factor analysis of the three domain ratings showed that a single factor could explain 85% of the variance.…”
Section: In-role Performancementioning
confidence: 89%
“…Evidence shows that the RPM can achieve a greater range of-and more accuratescores when compared with rating each student independently. 9 The three domain ratings were strongly correlated with one another (r = 0.71-0.84, P < .001). A principal components factor analysis of the three domain ratings showed that a single factor could explain 85% of the variance.…”
Section: In-role Performancementioning
confidence: 89%
“…** Figure 1 about here** As is customary in meta-analysis (e.g., Dudley et al, 2006;Salgado, 1998), composite correlation coefficients were obtained whenever more than one predictor measure had been used to assess the same constructs; such as in a study by Marcus, Goffin, Johnston and Rothstein (2007), where two different personality measures were employed to assess the FFM dimensions. Composite coefficients were also calculated where more than one criterion measure had been used; such as in research comparing the usefulness and psychometric properties of two methods of performance appraisal aimed at measuring the same criterion scales (Goffin, Gellatly, Paunonen, Jackson & Meyer, 1996).…”
Section: The Choice Of Predictor and Criterion Variablesmentioning
confidence: 99%
“…The Relative Percentile Method (RPM) formed the basis for the rating scale used to assess team learning, which provided a meaningful comparison point for behaviors occurring in previous weeks 25 . More specifically, teams responded collectively to two RPM items measuring: (1) exploratory and (2) exploitative learning activities.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…In the aforementioned TA training, we included coaching to calibrate TAs perceptions of what constitutes innovation before they completed their ratings (see appendix B). The RPM formed the basis for the rating scale used to measure innovation 25 . Team innovation was defined as the extent to which the team's prototype embodied both a) the existence of a novel, unique, and original idea, and b) the effective implementation of the idea and functionality of the prototype 21 .…”
Section: Methods and Proceduresmentioning
confidence: 99%